Reflections on state experiences in the IGAD region - Obila, C; Pop, A (Refugee Studies Centre, University of Oxford, 2020)
State-to-State exchanges in 2019 focused attention on what more is needed if governments in the IGAD region are to respond more effectively to high levels of internal displacement.